Lime pretreatment of maize stover and solubilization of pretreated solids by enzymatic hydrolysis and Clostridium thermocellum fermentation - Wang, Guanying; Zhang, Gang; Shao, Xiongjun (International Journal of Agricultural and Biological Engineering, 2024)
Lime pretreatment on maize stover was conducted with various pretreatment conditions selected by central composite design. Xylan and lignin contents in pretreated maize stover were relatively constant. Concentration of glucose monomer and oligomers decreased while concentration of xylooligomers increased in the pretreatment hydrolysate with increasing pretreatment intensity. The overall carbohydrate recovery was at least 85% for the conditions studied. Xylan removal during pretreatment was found to have a linear correlation with lignin removal. Pretreatment had a higher effect in enhancing carbohydrate solubilization for enzymatic hydrolysis than that for C. thermocellum fermentation. For all the pretreated solids, Clostridium thermocellum fermentation was found to result in much higher carbohydrate solubilization than enzymatic hydrolysis with a cellulase loading of 8 mg/g solids and a xylanase loading of 2 mg/g solids. Carbohydrate solubilization was found to have a linear correlation with lignin removal during lime pretreatment for both enzymatic hydrolysis and C. thermocellum fermentation. Considering the current challenges, this research provides a new idea for the industrial application of lignocellulosic biorefinery. Key words: central composite design; lime pretreatment; enzymatic hydrolysis; clostridium thermocellum; carbohydrate solubilizationDOI: 10.25165/j.ijabe.20241704.6571Citation: Wang G Y, Zhang G, Shao X J. Lime pretreatment of maize stover and solubilization of pretreated solids by enzymatic hydrolysis and Clostridium thermocellum fermentation. Int J Agric & Biol Eng, 2024; 17(4): 288–296.